Large HDL particles negatively associate with leukocyte counts independent of cholesterol efflux capacity: A cross sectional study in the population-based LifeLines DEEP cohort. (February 2022) - Groenen, Anouk G.; Bazioti, Venetia; van Zeventer, Isabelle A.; Chen, Lianmin; Groot, Hilde E.; Balder, Jan-Willem; Zhernakova, Alexandra; van der Harst, Pim; Rimbert, Antoine; Kuivenhoven, Jan Albert; Fu, Jingyuan; Westerterp, Marit
Abstract: Background and aims: Leukocytosis, the expansion of white blood cells, is associated with increased cardiovascular risk. Studies in animal models have shown that high-density lipoprotein cholesterol (HDL-c) suppresses leukocytosis by mediating cholesterol efflux from hematopoietic stem and progenitor cells. HDL-c showed a moderate negative association with leukocyte numbers in the UK Biobank and Multi-Ethnic Study of Atherosclerosis. Cholesterol efflux capacity of HDL (HDL-CEC) or HDL particle (HDL-P) number has been proposed as improved inverse predictor of CVD compared to plasma HDL-c. In the LifeLines DEEP (LLD) cohort (n = 962), a sub-cohort representing the prospective population-based LL cohort from the North of The Netherlands, we tested the hypothesis that HDL-CEC and HDL-P were associated with lower leukocyte counts. Methods: We carried out multivariable regression and causal mediation analyses (CMA) to test associations between HDL-c, HDL-CEC, or HDL-P and leukocyte counts. We measured HDL-CEC in THP-1 macrophages and HDL-P and composition using nuclear magnetic resonance. Results: HDL-c associated negatively with leukocyte counts, as did extra-large and large HDL-P, while HDL-CEC showed no association. Each one-standard deviation (SD) increase in extra-large HDL-P was associated with 3.0% and 4.8% lower leukocytes and neutrophils, respectively ( q  < 0.001). In contrast, plasma concentration of small HDL-P associated positively with leukocyte and neutrophil counts, as did small HDL-P triglycerides (TG) and total plasma TG. CMA showed that the association between S-HDL-P and leukocytes was mediated by S-HDL-TG. Conclusions: The association between HDL-P and leukocyte counts in the general population is dependent on HDL-P size and composition, but not HDL-CEC. Graphical abstract: Image 1 Highlights: High-density lipoprotein cholesterol (HDL-c) negatively associates with leukocyte counts independent of cholesterol efflux capacity of HDL (HDL-CEC). Extra-large and large HDL particles (HDL-P) negatively associate with leukocyte counts. The strong positive association between small HDL-P and leukocyte counts is mediated by HDL-triglycerides (TG). S-HDL-TG showed a strong positive correlation with total plasma TG.